Study Result of Straight Motion Through Worksheet Based on Guided Note Taking (GNT) by Setting Guided Inquiry Learning to Students X Class in Senior High School of Jember - I K Mahardika; I Gusti Kadek Dwi Septi Oktaviani; A Harijanto (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2020)
This research aims to influence the result of student learning about the straight motion and describe the science process skills of students for learning with setting by guided inquiry model with a worksheet based on Guided Note Taking (GNT). The kind of research was an experiment by randomized post-test only control group design. The population of this research is a class X IPA SMA Negeri Mumbulsari. Based on the results of the analysis science process skills of students in the class experiment can be described as very good with reaching an average value of 81,17%. Next up is an analysis of knowledge students' competence obtained the average value of knowledge students competence on the class experiment of 75,70 and grade control of 70,00. So it can be concluded that the guided inquiry model with a worksheet based on GNT influences the results of the cognitive learning of physics in learning about the motion straight in SMA Negeri Mumbulsari.